YOUNG GENERATION PERCEPTION AND PARTICIPATION IN THE DEVELOPMENT OF THE CREATIVE ECONOMY ECOSYSTEM IN TOMOHON CITY - Yani Handri Rumengan; Lidya N. Tengker; Margareth I. R. Rantung. (CV. Radja Publika, 2026)
This study aims to analyze the perceptions of the younger generation towards the potential of the creative economy in Tomohon City, identify the level and form of their participation, explore the factors that motivate and hinder their involvement, and formulate strategic policy recommendations for the Tomohon City Government. This study uses a qualitative approach with Kelurahan as a case study, involving in-depth interviews, participant observation, and documentation studies of the younger generation, Kelurahan officials, tourism Kelurahan managers, MSMEs, and related stakeholders in Tomohon City. The results show that the younger generation's perception of the potential of the creative economy is ambiguous because on the one hand they see great opportunities from the success of TIFF which recorded an economic turnover of IDR 92 billion and the achievement of Kakaskasen Dua Village as the winner of ADWI 2023, but on the other hand they are faced with the reality of the high youth unemployment rate which reaches 88 percent. The participation of the younger generation is still not optimal, limited to physical involvement in events and independent communities without a strategic role in development decision-making. Driving factors include the potential for economic income, pride in local culture, the availability of spaces for expression, capacity training programs, and recognition and appreciation from the local government. Meanwhile, inhibiting factors include low digital literacy, limited access to capital, minimal supporting infrastructure, lack of understanding of opportunities, high unemployment rates, and weak institutional coordination. This study recommends improving digital literacy, expanding access to capital, accelerating the development of creative hubs, integrating creative economy education, and strengthening institutions and coordination among stakeholders to encourage active participation of the younger generation in an inclusive and sustainable creative economy ecosystem in Tomohon City.